Revitalizing Distance Learning: MOOC For Improving The Quality of Training for Civil Servants - Widhanarto, Ghanis Putra; Prihatin, Titi; Haryono, Haryono; Kusumawardani, Seftia (Universitas Negeri Semarang, 2023)
The COVID-19 pandemic has had a widespread impact on the education and training sector. Central Java, a province with training management resources, is experiencing a crisis in training management today. The large number of training participants from the state civil apparatus (SCA) who come from various regions in Indonesia requires innovation and change despite the various limitations of managers who do not have a special education base. Training managers at BPSDMD for SCA training need to be strengthened by developing distance learning through MOOCs because it can overcome the problems of distance, time, and financing to organize training that is usually done offline. This MOOCs will also increase the trust of other government agencies by making BPSDMD a pilot local government-based MOOCs developer. This service is carried out through mentoring and training that focuses on improving the resources of training managers at BPSDMD Central Java Province. This training and mentoring activity was attended by 38 BPSDMD employees with an In-House Training scheme for two days. As a result, there was an increased understanding of MOOCs and its application, designing training programs, presenting training materials, and evaluating training programs. The skills of the trainees can be seen from the portfolios collected. This service is useful in developing BPSDMD training programs for SCA in Central Java.